Department of Animal Genetics and Breeding, College of Veterinary Science and A.H, Mhow, Dist- Indore, Madhya Pradesh, India. Pin Code-453446 - Savanur, Mahesh; Satyanarayan, K; Jagadeswary, V; Shree, J Shilpa (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
An ex-post facto research design was adopted to study the growth and composition of cattle markets in eastern dry zone of Karnataka. The study sample comprised of six cattle markets and two annual cattle fairs. Ten sellers, ten buyers and five brokers from each market and cattle fair were selected randomly. The study revealed that sale of cows and bullocks in Chikka ballapur were stagnant over the years, whereas in Mulbagal, market sale of bullocks decreased at 39.54%. Prices of both cows and bullocks increased substantially over the years in the study area. Price of cows increased at 14.2 per cent per annum in both the markets and rapid increase in price of bullock was seen in Mulbagal (15.27% per annum) market. Sale of bullocks as well as price was higher in May, June and July months while, cow sales were higher in May and June months and prices were higher in July and August. Efforts have to be made to stabilise sale and price by introducing fairly high competition through facilitating movement of animals to deficit areas.